2012
DOI: 10.1111/j.1462-5822.2012.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 mediates the disruption of adherens junctions to promoteEscherichia coliK1 invasion of brain endothelial cells

Abstract: The transcellular entry of E. coli K1 through human brain microvascular endothelial cells (HBMEC) is responsible for tight junction disruption, leading to brain edema in neonatal meningitis. Previous studies demonstrated that outer membrane protein A (OmpA) of E. coli K1 interacts with its receptor, Ecgp96 to induce PKC-α phosphorylation, adherens junction (AJ) disassembly (by dislodging β-catenin from VE-cadherin), and remodeling of actin in HBMEC. We report here that IQGAP1 mediates β-catenin dissociation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…These reports of cytokinesis-and centralspindlin-independent RacGAP1 functions suggest that RacGAP1 has a broader range of functions than previously anticipated. In this context, IQGAP1 is known to localise at cell-cell junctions (Krishnan et al, 2012;Lehtonen et al, 2005;Noritake et al, 2004) and cell-cell junction proteins were identified as IQGAP1-associated proteins (e.g. b-catenin) (supplementary material Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…These reports of cytokinesis-and centralspindlin-independent RacGAP1 functions suggest that RacGAP1 has a broader range of functions than previously anticipated. In this context, IQGAP1 is known to localise at cell-cell junctions (Krishnan et al, 2012;Lehtonen et al, 2005;Noritake et al, 2004) and cell-cell junction proteins were identified as IQGAP1-associated proteins (e.g. b-catenin) (supplementary material Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to triggering the internalization of E. coli K1 into HBMECs, the binding of OmpA to its gp96 homologue receptor stimulates inducible nitric oxide synthase and nitric oxide production, which enhances the generation of cyclic GMP (237). This increase in cyclic GMP activates protein kinase C␣ (237), which leads to a Ras GTPase-activating-like protein (IQGAP1)-mediated dissociation of ␤-catenin from vascular endothelial cadherin at adherens junctions (238). Immunofluorescence experiments demonstrated that vascular endothelial cadherin was redistributed from the intercellular junctions to the sites of bacterial attachment (239).…”
Section: Paracellular Penetration Of Brain Microvascular Endothelial mentioning
confidence: 99%
“…These results along with invasion data suggest that the CNF1 secreted by E44 into macrophages exert excessive actin redistribution, which partially results in the formation of microspikes, thereby inducing effective sequestration of actin and resulting in the unavailability of the actin required for the optimal invasion of E44. 13,26,28 In contrast, Dcnf1 could not induce microspikes due to lack of CNF1, and thus, all actin in the cells are available for efficient bacterial invasion compared to E44. This is a novel observation that CNF1, a bacterial virulence factor, plays a role in limiting the internalization of the bacteria into the host cell by modulating actin availability.…”
Section: E Colik1 Internalization Induces a Greater Number Of Microsmentioning
confidence: 99%
“…We have previously demonstrated that E. coli K1 recruits actin filaments underneath the bacterial attachment sites. 13,[26][27][28][29] Therefore, we treated RAW 264.7 macrophages with various E. coli K1 strains listed above and then stained for actin filaments with phalloidin. E44, as expected, induced actin filament remodeling in these cells beneath the bacterial attachment sites; however, E44 also triggered more microspikes that protruded from RAW 264.7 macrophages compared to uninfected cells ( Fig.…”
Section: E Colik1 Internalization Induces a Greater Number Of Microsmentioning
confidence: 99%